(untitled) (Bulletin of Kharkiv National University of Internal Affairs, 2019)
The current state of activity of the Armed Forces of the Baltic States such as Latvia, Lithuania and Estonia has been studied. The experience of the Armed Forces of these countries in ensuring collective defense, security and peace in accordance with NATO standards has been analyzed. It is stated that the National Armed Forces of the Republic of Latvia is a group of troops intended to protect the fundamental freedoms, independence and territorial integrity of the state. It’s a part of the Ministry of Defence of Latvia. It is emphasized that the Armed Forces of the Republic of Lithuania are a state military organization whose purpose is to protect the territorial integrity and inviolability of the state. It is a structural unit of the Ministry of National Defence Republic of Lithuania. It is noted that the Armed Forces of Estonia (Defence Forces) is a military organized unit of the Executive authority, which is headed by the government of the Republic and the Ministry of Defence of Estonia. It is stated that the activities of the Armed Forces of the Baltic States are carried out on the principle of collective defence of the North Atlantic Treaty Organization, which task is to protect the member States from military threat. Based on the analyzed experience of the Baltic States’ Armed Forces, it has been concluded that the effective functioning and activities of the Armed Forces depends on a clear definition of the main priorities in the field of defenсe, chains of international community and valid logistical support. It is noted about the possible implementation of certain positive provisions regarding the transformation about the integrated leadership system of the defenсe forces and military management in the Armed Forces in accordance with NATO standards and the provision of advisory assistance.